Severe Jaundice in Two Children with Kawasaki Disease: A Possible Association with Gilbert Syndrome - Fretzayas, Andrew M.; Karpathios, Themistocles; Moustaki, Maria; Yiallouros, Panayiotis K.; Sharifi, Fariba; Attilakos, Achilleas V.; Papadopoulou, Anna (My University, 2012)
Kawasaki disease is a systemic vasculitis, mainly encountered in children. It may affect any organ. Acute cholestasis and severe obstructive jaundice is an atypical manifestation of the disease. We herein present two children with Kawasaki disease and severe direct hypebilibirunemia who also were homozygous and heterozygous respectively for the (TA)7 promoter polymorphism of Gilbert syndrome. Intravenous immunoglobulin was administered to both patients at the acute phase of the disease and the fever remitted within 24 hr following the immunoglobulin administration. Furthermore oral aspirin at a dose of 80-100 mg/kg/24 hr was also given. The first child did not develop any coronary ectasia or aneurysm, whereas dilation of the right coronary artery was identified in the second child, one month after the disease onset. We discuss the possible contribution of Gilbert syndrome to the development of jaundice in our patients. 2012 The Korean Academy of Medical Sciences.
Keywords: Kawasaki Disease; Gilbert Syndrome; Jaundice; Acute Cholestasis